À qui appartient la montagne ? Trajectoires de la propriété collective en Slovaquie - Michel Lompech (Revue de Géographie Alpine)
The agricultural landscape of the Slovakian mountains is defined by a particular type of agricultural and forestry community property: the urbariat forestry association. The history of this establishment tells of conflicts between the regimes of property of the estate (public or seigniorial) and peasant property for the control of forestry resources. This article explains how this method of community management has been incorporated into the socialist system and how it has been restored during a transition stage. The vitality of the urbariat is a testament to the strength of mobilisation among local actors.